Parallel dynamic storage allocation algorithms - Iyengar, A. (Parallel and Distributed Processing, 5th IEEE Symposium On, 1993)
A dynamic storage allocator manages space for objects whose lifetimes are not known by the system at the time for their creation. This paper examines parallel dynamic storage allocation algorithms. Three new algorithms, multiple free list fit I, modified quick fit, and multiple free list fit II, are presented which outperform all previous algorithms we tested. The performances of the three algorithms differ when the percentage of requests for large blocks is high. Multiple free list fit I is the fastest algorithm when large blocks of many different sizes are requested. Multiple free list fit II is the fastest algorithm when large blocks of only a few different sizes are requested.< >